Community Organizing for Climate Change Adaptation and Mitigation in Kalikatir Village, Gondang Sub District, Mojokerto Regency - Mohammad Ansori; Maufidah Nazilatul Habibah (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
This research focused on the following things; a) How are the problems resulting from climate change to the quality of the environment and people in Kalikatir village? b) How are strategies in solving the problem of climate change through adaptation and mitigation efforts? c). What was the meaning of da’wah in this community organizing? Researchers used the Participatory Action Research (PAR) method along with Participatory Rural Appraisal (PRA) techniques for data mining. The dynamics of community organizing included inculturation, knowing, understanding, planning, action, monev, reflection, and report. The results of the research showed that the local climate change presents various problems in the disaster of natural resources, food resistance, economy, and health sectors. Community organizing of people produced a